2019
DOI: 10.1039/c9nr02251a
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oxygen plasma treatment on carrier transport and molecular adsorption in graphene

Abstract: Transport property variation in O2 plasma treated graphene and related enhancement in NH3 sensing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Energetic plasma treatment commonly removes organic capping material (e.g., CTAB bilayer) to improve surface modification in AuNPs. [10][11][12][13] We reported the morphological and spectral changes of single AuNRs for various plasma treatment times in our previous study. 14 Furthermore, we demonstrated that the silica coating in AuNRs@mSiO 2 enhances the AuNR core stability against oxygen plasma treatment.…”
mentioning
confidence: 99%
“…Energetic plasma treatment commonly removes organic capping material (e.g., CTAB bilayer) to improve surface modification in AuNPs. [10][11][12][13] We reported the morphological and spectral changes of single AuNRs for various plasma treatment times in our previous study. 14 Furthermore, we demonstrated that the silica coating in AuNRs@mSiO 2 enhances the AuNR core stability against oxygen plasma treatment.…”
mentioning
confidence: 99%
“…This O atoms create the D and D 0 peaks of graphene, which are similar to those of the O 2 plasma-treated graphene. 33,34 It is also accurately demonstrated that Al generated by Al 2 O 3 decomposition does not lead to graphene-loss because graphene is observed across the whole surface of all samples over 1200 C. From the Raman data alone, as shown in Fig. 1b, we can assume that the decomposed Al 2 O 3 substrate affects the D and D 0 peak of graphene, but it does not lead to grapheneloss.…”
Section: Resultsmentioning
confidence: 62%
“…6,17 Both the mobility and the carrier concentration are similar to those reported earlier. 8,10 GISFET characterization…”
Section: Graphene-based Fet Characterizationmentioning
confidence: 99%
“…This issue can be addressed by fabricating graphene-based ISFETs (GISFETs), which uses impervious graphene as the ion sensing layer, which is typically coated with an ion selective membrane (that prevents damage to the graphene layer itself). Due to its high carrier mobility and atomically thin nature, graphene has demonstrated excellent ionic sensitivity, [6][7][8][9] making it very well suited for ion efflux measurements.…”
Section: Introductionmentioning
confidence: 99%